The Paris Express : a novel [large type] - Donoghue, Emma, 1969- (Thorndike Press large print dynamic drama., 2025)
"Based on an 1895 disaster that went down in history when it was captured in a series of surreal, extraordinary photographs, The Paris Express is a propulsive novel set on a train packed with a fascinating cast of characters who hail from as close as Brittany and as far as Russia, Ireland, Algeria, Pennsylvania, and Cambodia. Members of parliament hurry back to Paris to vote; a medical student suspects a girl may be dying; a secretary tries to convince her boss of the potential of moving pictures; two of the train's crew build a life away from their wives; a young anarchist makes a terrifying plan, and much more"--